Don't Fret: The Worship Leaders Pocketbook (Hallett Cove, SA : Annette Purdey, 2020)
There have been many inspiring books written about worship, but where can you find advice as a leader who shapes your church's worship week by week? This book aims to address that need. It is a quick to read, organized and informative guide on the shaping and presentation of worship in Australia today. Don't Fret provides guidance on service planning, direction, flow and theology, with the often assumed but frequently ignored skills of music presentation, platform ministry and service leadership, also addressed. It is a practical guide book for all involved in church leadership (both lay and ordained).The material for this book grew out of Don's thirty years of experience as a musician and worship leader, including 16 years as an ordained minister in the Uniting Church in South Australia.
Keywords: Theology, Practical; Philosophy and religion; Worship